EVOLUTION OF APPROACHES IN TERMINOLOGY: FROM TRADITIONAL TO MODERN - Bakhodirova Gulrukh Bakhodirovna (Modern American Journals, 2025)
This research investigates the historical and theoretical evolution of terminology science from traditional prescriptive models to modern cognitive, functional, and communicative approaches. By examining the Uzbek linguistic context alongside international developments, the work illuminates the main stages, driving factors, and impacts of technological transformation in terminology. The study applies comparative analysis of classic and contemporary sources, corpus exploration, and expert interviews. Results emphasize the increasing role of interdisciplinarity, digital integration, and sociocognitive paradigms in shaping effective terminological systems. Recommendations are provided for Uzbek and global practice.
Keywords: Terminology, evolution, Uzbek linguistics, standardization, cognitive linguistics, IMRaD, interdisciplinarity.